Hemangioendotelioma Kapasiforme mediastinal complicado com síndrome de Kasabach-Merrit: relato de caso - Luanna Ribeiro Campos dos Santos Novais; Alef de Carvalho Vieira; Bruno da Costa Rocha; Erika Patricia Barbosa Correia; Braulio Xavier Pereira Silva-Neto; Breno Soares de Andrade Wanderley; Amanda Gordiano Machado; Mila Simões Alves (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVES: This paper reports the case of a child diagnosed with mediastinal kaposiform hemangioendothelioma (KHE) and Kasabach-Merritt Syndrome at a referral hospital in Salvador, Bahia, Brazil. CASE REPORT: A two-month-old with a history of cyanosis and nasal congestion had an echocardiogram with findings consistent with pericardial effusion. The patient underwent multiple pericardial drainage procedures and was eventually sent to a pediatric referral center in the city of Salvador. Contrast-enhanced computed tomography images showed a mediastinal mass, which was resected. Postoperative pathology revealed the patient had a KHE. He was also suspected with Kasabach-Merritt syndrome due to consumption coagulopathy. Corticoid therapy and chemotherapy with vincristine were performed. The patient progressed well and was discharged and placed on outpatient follow-up, without recurrence of symptoms. COMMENTS: KHE is rare and aggressive, although with a benign histopathology. It can complicate with consumption coagulopathy, characteristically seen in Kasabach-Merritt syndrome.